'This is Not a Pipe'?: Reflexivity, fictionality and dialogism in Sembène's films. (1st October 2016) - Repinecz, Jonathon
The work of Senegalese film-maker Ousmane Sembène is often analysed in terms of its highly ideological and social realist mode. This paper questions the relevance of a one-way 'film as message' model by demonstrating how Sembène's films thematize the limits of meaning. His work systematically emphasizes the dialogical construction of meaning, whether of important symbols like the mask in La Noire de .../Black Girl, or of the films themselves as objects circulating in society. Self-reflexive strategies like posters and cameos by Sembène call the viewer's attention to the constructedness of the ideological message and the arbitrariness of the film as sign. Sembène's films are still a call to action, but they are also a call to thought about the factitiousness of narrative, and to dialogue about the work of interpretation.